The Design of Door Handles for Civil Aircraft Cabin Doors Utilizing Addictive Manufacturing for Aerospace Component Manufacturing - Samsaimon, Mohamad Shahriz Asraf; Wahab, Md Saidin (Progress in Aerospace and Aviation Technology, 2023)
Door handles, usually referred to as "door knobs," are the handles used to open and close a door. On a variety of doors, including the outside doors of homes and businesses, the interior doors of homes, the doors of cupboards and cabinets, and the doors of vehicles, door handles are a common fixture. There are numerous types of door knobs, each of which has a distinct function. Significant numbers of door handles, especially those made for residential and commercial doors, either incorporate latching or locking mechanisms into their design or are manufactured to be compatible with a variety of standard door latching and locking systems. Door handles can be created from a bewildering variety of materials. Brass, porcelain, cut glass, wood, and bronze are examples of various materials. The cabin doors of a civil aircraft serve as the key determinant of the user's first impression because they are the user's first point of contact with the aircraft. Doors must consequently be self-explanatory as to their operability and function. This must not represent the first manual and/or technical difficulty when entering a civil aircraft and ensure that all passengers may board the aircraft safely. The term "additive manufacturing" refers to a variety of techniques that begin with a digital 3D model and result in a three-dimensional object. During these operations, material is mixed, deposited, or created layer by layer under the computer's control. Numerous past studies and research have exclusively focused on prototypes and non-critical components when making aerospace components and parts utilizing additive manufacturing. As the technology of additive manufacturing (AM) has advanced and evolved rapidly, more research is being undertaken on the significance of replacing existing methods of producing key parts and components with AM. This research will heavily rely on SolidWorks software to replicate the existing product into a 3D model, which will then be redesigned to make it easier to produce using the additive manufacturing process so that the product can be used immediately without the need for an assembly process by eliminating all design from the component. The 3D model of the new door handles of civil aircraft designs was analyzed with SolidWorks software and found to perform better compared to the original cabin door handle in terms of the amount of displacement and the value of the safety factor.